Rancang Bangun CNC Router 3 Axis Ukir Kayu Untuk Kerajinan Kaligrafi - Sugeng Dwi Riyanto; Muhamad Yusuf; Riyani Prima Dewi; Robbihim Nurdiansyah (Infotekmesin, 2024)
The Indonesian wood industry is diverse, with wood carving being one of its most popular products. However, the manual wood carving process is not suitable for large-scale production. To address this challenge, a new tool has been developed to increase the production of wood crafts, especially calligraphy carving. This tool is a 3-axis wood carving CNC router machine controlled by a computer and smartphone. The CNC router machine was designed using the CNC Shield V3 and the Arduino Uno R3 motor driver, A4988 as a stepper motor controller. The mechanism applied includes creating vector images programmed with gcode, controlling and engraving calligraphy through software on computers and applications on smartphones with Bluetooth HC – 05 communication with a maximum distance of smaller than 10 meters. Based on control data by computer testing geometry testing circle dimensions of 58 mm x 56 mm and feed rates of 5 mm/sec, 8 mm/sec and 10 mm/sec with engraving times of 01:12, 00:48 and 00:42. Testing Muhammad's carving with dimensions of 100 mm x 100 mm and feed rates of 5 mm/sec, 8 mm/sec and 10 mm/sec with engraving times of 05:22, 03:45 and 03:24. Tests for cutting 12 mm thick MDF wood with a depth 1.5 mm and a feed rate of 5 mm/sec cuts 8 rounds for 13:12 min/sec. The control data by smartphone testing the geometry of the circle with dimensions of 50 mm x 50 mm and a feed rate of 500mm/min with a carving time of 58:43 minutes. Testing Muhammad's engraving dimensions of 70mm x 60mm and feed rates of 500 mm/min, 800 mm/min, and 1000 mm/min with engraving times of 54:34, 39:25, and 35:28. The test for cutting 12 mm thick MDF wood with a depth of 1.5 mm and a feed rate of 500 mm/min-cut 8x rounds for 10:21 minutes/second.